Heat shock factor 2 regulates oncogenic gamma-herpesvirus gene expression by remodeling the chromatin at the ORF50 and BZLF1 promoter - Cutrone, Lorenza; Djupenström, Hedvig; Peltonen, Jasmin; Martinez, Klimova Elena; Corso, Simona; Giordano, Silvia; Sistonen, Lea; Gramolelli, Silvia (Public Library of Science (PLoS), 2025)
The Human gamma-herpesviruses Kaposi's sarcoma herpesvirus (KSHV) and Epstein-Barr virus (EBV) are causally associated to a wide range of cancers. While the default infection program for these viruses is latent, sporadic lytic reactivation supports virus dissemination and oncogenesis. Despite its relevance, the repertoire of host factors governing the transition from latent to lytic phase is not yet complete, leaving much of this complex process unresolved. Here we show that heat shock factor 2 (HSF2), a transcription factor involved in regulation of stress responses and specific cell differentiation processes, promotes gamma-herpesvirus lytic gene expression. In lymphatic endothelial cells infected with KSHV and in gastric cancer cells positive for EBV, ectopic HSF2 enhances the expression of lytic genes; While knocking down HSF2 significantly decreases their expression. HSF2 overexpression is accompanied by decreased levels of repressive histone marks at the promoters of the lytic regulators KSHV ORF50 and EBV BZLF1, both characterized by poised chromatin features. Our results demonstrate that endogenous HSF2 binds to the promoters of KSHV ORF50 and EBV BZLF1 genes and shifts the bivalent chromatin state towards a more transcriptionally permissive state. We detected HSF2 binding to the ORF50 promoter in latent cells, in contrast, in lytic cells, HSF2 occupancy at the ORF50 promoter is lost in conjunction with its proteasomal degradation. These findings identify HSF2 as a regulator of gamma-herpesvirus lytic gene expression in latency and offer new insights on the function of this transcription factors at poised gene promoters, improving our understanding of its role in differentiation and development.